SYNTHESIS AND OPTICAL CHARACTERIZATION OF STRONTIUM OXIDE NANOPARTICLE (International Journal of Food and Nutritional Sciences, 2022)
Synthesis of strontium oxide is very remarkable for its applications in electrodes forgas sensors, solar cells, lithium-ion-batteries, transistors, super capacitors and semiconductors. Thisstudy is intended to synthesize SrO nanoparticle using a sol gel method. The crystalline nature, size,and morphological structure of SrO powder sample were characterized by techniques such as XRD,FTIR, SEM with EDAX, UV-Vis Spectroscopy, and PL spectral analysis. X-ray diffraction peaksindicate that the nanoparticles are crystalline in nature. The crystallite size of strontium oxidenanoparticles was calculated using Debye-Scherrer formula. The crystalline sizes are about 47.06 nm.The surface was scanned using SEM and EDAX and the results showcased the morphology and purityof the prepared sample. FTIR spectrum of strontium oxide confirmed the phase formation. Theabsorption peak exhibited at 280nm in UV region. In addition, it is demonstrated that the band gapenergy was calculated to be 2.30eV. Photoluminescence study shows that the prepared nanoparticlehaving highefficient light emitting properties that could be suitably used for various lightingapplications.